2002
DOI: 10.1146/annurev.med.53.082901.103952
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2: A Therapeutic Target

Abstract: Cyclooxygenase (COX), also known as prostaglandin endoperoxide synthase, is the key enzyme required for the conversion of arachidonic acid to prostaglandins. Two COX isoforms have been identified, COX-1 and COX-2. In many situations, the COX-1 enzyme is produced constitutively (e.g., in gastric mucosa), whereas COX-2 is highly inducible (e.g., at sites of inflammation and cancer). Traditional nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit both enzymes, and a new class of COX-2 selective inhibitors (COXI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
390
0
9

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(404 citation statements)
references
References 125 publications
5
390
0
9
Order By: Relevance
“…COX-2 is not detected in most normal tissues but is rapidly induced in response to mitogens, cytokines and tumor promoters, leading to increased accumulation of prostanoids in neoplastic and inflamed tissues (Subbaramaiah et al, 1996). COX-2 is highly inducible by the oncogenes ras and scr and other cytokines at the sites of inflammation and cancer (Kam and See, 2000;Turini and DuBois, 2002;Church et al, 2003). Previous studies have shown that most cancer cells are found to exhibit over-expression of COX-2, which can stimulate cellular division and angiogenesis and inhibit apoptosis (Dempke et al, 2001).…”
Section: Cox-2 and Colon Cancermentioning
confidence: 99%
“…COX-2 is not detected in most normal tissues but is rapidly induced in response to mitogens, cytokines and tumor promoters, leading to increased accumulation of prostanoids in neoplastic and inflamed tissues (Subbaramaiah et al, 1996). COX-2 is highly inducible by the oncogenes ras and scr and other cytokines at the sites of inflammation and cancer (Kam and See, 2000;Turini and DuBois, 2002;Church et al, 2003). Previous studies have shown that most cancer cells are found to exhibit over-expression of COX-2, which can stimulate cellular division and angiogenesis and inhibit apoptosis (Dempke et al, 2001).…”
Section: Cox-2 and Colon Cancermentioning
confidence: 99%
“…In human keratinocytes, PI3K regulates UV-B light induced cyclooxygenase-2 (COX-2) expression through activation of AKT and consequential inhibition of glycogen synthase kinase 3β (GSK3β) (Tang et al, 2001;Bachelor et al, 2005;Sheu et al, 2005;Wu et al, 2005). COX-2 gene responds to a diverse range of stimuli from growth factors or cytokines to physical or chemical stress by increasing expression (Smith, 2000;Hinz and Brune, 2002;Turini and DuBois, 2002;Warner and Mitchell, 2004). Several signaling transduction pathways have been shown to regulate COX-2 gene expression, including the Mitogen-Activated Protein Kinases (Smith, 2000), Protein Kinase A (Choudhary et al, 2004;Pino et al, 2005) or Protein Kinase C (Xuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…COX-1 and COX-2 catalyze the rate-limiting step in prostanoid synthesis, converting arachidonic acid into PGH 2 , the precursor of a family of bioactive prostanoids, including thromboxane (TXA 2 ) and prostaglandins (PGs) [1,2]. COX-1 is a widely expressed constitutive enzyme that participates in tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, COX-2, the inducible isoform, is expressed at low levels in most tissues but can be stimulated by LPS, growth factors and cytokines, such as TNF-a and interleukin-6 (IL-6) [3,4], being implicated in inflammatory processes, including atherosclerosis, rheumatoid diseases and carcinogenesis [5 -7]. A direct role for COX-2 in atherosclerosis can be inferred from studies showing significant expression in human atherosclerotic lesions [8][9][10], as well as COX-2-derived PGE 2 increase in subclinical atherosclerosis [11,12]. Paradoxically, recent evidence points to a protective function of this enzyme in cardiomyocytes subjected to oxidative stress [13] and also in late preconditioning after ischemia/reperfusion injury [14].…”
Section: Introductionmentioning
confidence: 99%